Catabolism of lysine in Penicillium chrysogenum leads to formation of 2-aminoadipic acid, a precursor of penicillin biosynthesis. - Esmahan, C (1994)
Penicillium chrysogenum L2, a lysine auxotroph blocked in the early steps of the lysine pathway before 2-aminoadipic acid, was able to synthesize penicillin when supplemented with lysine. The amount of penicillin produced increased as the level of lysine in the media was increased. The same results were observed in resting-cell systems. Catabolism of [U-14C]lysine by resting cells and batch cultures of P. chrysogenum L2 resulted in the formation of labeled saccharopine and 2-aminoadipic acid. Formation of [14C]saccharopine was also observed in vitro when cell extracts of P. chrysogenum L2 and Wis 54-1255 were used. Saccharopine dehydrogenase and saccharopine reductase activities were found in cell extracts of P. chrysogenum, which indicates that lysine catabolism may proceed by reversal of the two last steps of the lysine biosynthetic pathway. In addition, a high lysine:2-ketoglutarate-6-aminotransferase activity, which converts lysine into piperideine-6-carboxylic acid, was found in cell extracts of P. chrysogenum. These results suggest that lysine is catabolized to 2-aminoadipic acid in P. chrysogenum by two different pathways. The relative contribution of lysine catabolism in providing 2-aminoadipic acid for penicillin production is discussed.